Hubungan minat membaca dan kebiasaan membaca dengan keterampilan menulis teks eksplanasi kelas v sekolah dasar - Yola Ahza Aqilah; Jenny Indrastoeti Siti Poerwanti; Supianto Supianto (Universitas Sebelas Maret, 2024)
This study aims to find out the relationship between reading interest and reading habits with the writing skills of the explanatory text students of class V SD N Bugel 02 Salatiga 2022/2023. This research uses a quantitative approach to correlational research models. This research sample is students of class V SD N Bugel 02. Data collection techniques used are questionnaires and tests. The validation used is expert validation and instrument validity test. Data analysis was carried out by descriptive statistics and multiple correlation analysis. The results of the study indicate that students’ reading interests are low, students’ reading habits are low, and student’s writing skills of the explanatory text are moderate and all three have strong, positive, and significant correlations. It is hoped that this research can provide information regarding students’ reading interests, reading habits, and the writing skills of the explanatory text. These results should be taken into consideration by teachers and schools to improve the efforts that have been carried out by not only considering the application of literacy but also the cultivation of interest and habits in students so that in the future students can implement these experiences as supporting efforts writing skills.